UPAYA PEMERINTAH INDONESIA DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA INDONESIA NONPROSEDURAL DI LUAR NEGERI - I Komang Agung Sanjaya (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study aims to (1) examine and analyze the form of legal protection provided by the Indonesian Government to non-procedural Indonesian Migrant Workers (TKI) working abroad, and to what extent the mechanism is able to guarantee the fulfillment of their basic rights even though their departure is not through official or legal channels and (2) to examine and analyze the obstacles faced by the Indonesian Government in providing legal protection to non-procedural TKI abroad, both those originating from national and international legal aspects, diplomatic limitations, and socio-political conditions in the country of placement. This study uses a normative legal approach with a conceptual method and a statutory regulatory approach. The data sources used include primary, secondary, and tertiary legal materials, obtained through literature studies. The results of this study indicate that legal protection for non-procedural Indonesian Migrant Workers (TKI) abroad has not been running optimally. Non-procedural TKI who depart without going through official channels do not receive adequate protection because they are not registered in the formal employment system. Existing laws and regulations, such as Law Number 18 of 2017, do not explicitly regulate the protection mechanism for them, so the state tends to take reactive steps when problems arise in the field. The protection provided is generally limited to repatriation assistance or handling emergency cases. On the other hand, various obstacles hinder the effectiveness of protection, including the absence of legal norms, limited diplomatic relations with the destination country, and an unfavorable socio-political situation. These conditions make non-procedural TKI very vulnerable to exploitation, violence, and human rights violations. A more inclusive policy is needed so that all Indonesian migrant workers, including non-procedural ones, continue to receive adequate legal protection.